COVID-19 appropriate behavior: Are the health care workers of Arunachal Pradesh competent enough to fight the pandemic? - Boro, Pallavi; Debarshi Paul; Mandula Prashanth Kumar; Kimo Ori; Anoop Dev (Asian Journal of Medical Sciences, 2022)
Background: COVID-19 is caused by coronavirus, first identified in Wuhan, China in December 2019, spread rapidly across international borders, and was declared pandemic on March 11, 2020. Occupation hazards such as close patient contact, suboptimal hand washing, inadequate use of personal protective equipment (PPE), and breach in infection control measures pose higher risk to health care workers (HCWs). Aims and Objectives: The objectives of the study are as follows: (1) To assess knowledge, beliefs, and practices of HCWs of a tertiary care hospital in Arunachal Pradesh regarding COVID appropriate behavior. (2) To create awareness and thereby prevent the spread of infections. Materials and Methods: A stratified sampling technique was applied to identify the study participants. A pre-tested and semi-structured questionnaire was administered to assess their knowledge, beliefs, and practices toward COVID-19. All departments (study units) were enlisted, all the HCWs were stratified according to their profession, for example, doctors, nurses, pharmacists, laboratory technician, and other HCWs. From each stratum, HCWs were randomly selected using simple random sampling and interviewed. Results: We found, 96.18% wore mask properly, 74.81% maintained physical distancing, and 55.34% greeted without physical contact while only 24.05% maintained respiratory hygiene. Mask was observed to be the most commonly known preventive measure (85.5%), followed by hand hygiene (69.47%), physical distancing (56.49%), and PPE kits (17.56%). It was observed that 53.44% of HCWs relied on government source of information. Conclusion: Most of the HCWs were practicing COVID appropriate behavior and the vaccination coverage was high among the HCWs (up to 2nd dose).